Nerón como personaje de tres tragedias españolas del siglo XIX* - Martín Puente, Cristina (Cuadernos de Filología Clásica. Estudios Latinos, 2005)
Roman Emperor Nero ist present in three XIXth century Spanish tragedies: La muerte de Nerón by Benito Vicens y Gil de Tejada, Nerón by Florencio Moreno Godino y Nerón by Juan Antonio Cavestany. These authors select very specific historical episodes and characters from the works of Tacitus, Suetonius and Dio Cassius and add invented facts and characters in order to achieve greater dramatism in their plays.